Oral treatment with 10% potassium iodide solution for refractory cutaneous-disseminated sporotrichosis in an immunocompetent adult: Case report - Zhuang, Kaiwen; Dai, Yaling; Zhou, Yike; Ke, Yujing; Ran, Xin; Ran, Yuping (Frontiers in Microbiology, 2022)
Sporotrichosis has multiple clinical manifestations, and its cutaneous-disseminated form is uncommon and, in most cases, related to immunosuppressive conditions. We report the case of a 47-year-old male patient who presented with multiple cutaneous nodules and ulcers on the left upper limb and the right thigh, with no other comorbidities. Until the diagnosis was confirmed, the patient was initially given empiric antifungal treatment with itraconazole, which showed unsatisfactory results at a local hospital. Then, he was treated with voriconazole, which led to the slow improvement of his skin lesions. At one point during the voriconazole treatment course, the patient briefly self-discontinued voriconazole for economic reasons, and the lesions recurred and worsened. The patient was finally diagnosed with cutaneous-disseminated sporotrichosis based on the isolation and identification of Sporothrix globosa. Susceptibility testing revealed that the isolate was resistant to itraconazole, fluconazole, voriconazole, terbinafine, and amphotericin. Considering the patient's poor financial condition, potassium iodide was administered. After 1-month of therapy with potassium iodide, he reported rapid improvement of his skin lesions. The patient continued potassium iodide treatment for another 5 months until the full resolution of lesions was achieved.